MENTAL FORAMEN TOPOGRAPHY IN DENTATE SUBJECTS - A RETROSPECTIVE STUDY BY REVIEW OF THE LITERATURE - Ovidiu Romulus Gherghiţă; Vanda Roxana Nimigean; Suzana Carmen Cismas; Victor Nimigean (Romanian Society of Oral Rehabilitation, 2019)
Aim of the study: to determine the position of the mental foramen in relation to the mandibular premolar teeth. The mental foramen is a landmark for anaesthesia in dental medicine and an anatomical obstacle in placing dental implants. The determination of the anatomical landmarks for the location of the mental foramen and the variations regarding its topography are important for mandibular dentoalveolar surgery. Material and methods: for this study we analyzed 39 abstracts of scientific papers, 43 in extenso articles, using the data bases of Google Scholar, Embase, PubMed and Medline, and additionally we consulted 8 anatomy books. Results: the results we obtained showed similarities among most of the accessed studies, but also certain differences. The most frequent variations related to the topography of the mental foramen were in the sagittal (horizontal) plane. According to most authors, in the anterior-posterior mandibular plane, the mental foramen is located, in most cases, between the two lower premolars or in the axis of the second premolar, and in the vertical plane it is located inferior to the apices of these teeth. Conclusions: a precise determination of the position of the mental foramen ensures therapeutic success of oral rehabilitation in the mandibular premolar area.